Sistem Manajemen Keselamatan dan Keamanan Kerja Produksi Kapal pada Galangan Berskala Mikro di Barombong Kota Makassar - Muhammad Iqbal Nikmatullah; Zulkifly Zulkifly; Syerly Klara; Baharuddin Baharuddin; Rahimuddin Rahimuddin; Andi Haris Muhammad; M. Rusydi Alwi; Surya Haryanto; Andi Husni Sitepu; Haryanti Rivai; Faisal Mahmuddin; Hasnawiyah Hasan; Balqis Shintarahayu (Faculty of Engineering UNHAS, 2022)
The community paradigm regarding the use of equipment that supports work safety and security still considers it disturbing the flexibility and flexibility of working. People have always assumed that they, and even those before them, were able to work safely and safely without the use of such equipment. This activity aims to provide an understanding of risk mitigation if problems occur in the ship production work process at CV's shipyard. Deka Cipta Sarana which is located in Barombong, Makassar City, as well as an introduction to work safety and security equipment and equipment, as well as understanding how to use it optimally. The implementation of this activity involved 15 workers at the shipyard location. Based on the results of the analysis of the questionnaire data distributed before and after the implementation of the activity, it was found that there was an increase in worker awareness in the implementation of the occupational safety and security management system. Understanding of risk mitigation of ship production work processes increased from 33% to 60% and understanding of the use of safety and security equipment and equipment increased from 27% to 67%.